Active Surveillance in Metastatic Renal Cell Carcinoma (Journal of Kidney Cancer, 2024)
Metastatic renal cell carcinoma (mRCC) is a heterogenous disease with a variable clinical course. While therapies for treatment of this condition have progressed, they are not without toxicity. In some patients, active surveillance (AS) of this disease is increasingly considered to delay its toxicity. This article seeks to review the literature and discuss management of metastatic renal cell carcinoma, specifically regarding upfront AS, the role of radiation therapy in delaying systemic therapy, and surveillance after initial treatment with systemic therapy. Median time on AS prior to initiation of systemic therapy ranged from 14 to 60 months across studies. AS is appropriate to offer in favorable or intermediate risk, asymptomatic, and systemic treatment naïve patients with mRCC.